Moving to Jobs: The Role of Information in Migration Decisions - Wilson, Riley (Journal of Labor Economics, 2021)
This paper exploits county-level variation in exposure to news about labor markets impacted by fracking to show that access to information about employment opportunities affects migration. Exposure to newspaper articles about fracking increased migration to areas mentioned in the news by 2.4% on average, concentrated among young, unmarried, less educated men. Commuting also increased, sentiment of the news matters, and TV news has an impact. Google searches for “fracking” and names of states specifically mentioned spike after news broadcasts about fracking. Counties experiencing weak labor markets are the most responsive, suggesting that these areas see large benefits to information provision.